2018
DOI: 10.4184/asj.2018.12.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Changes in Sagittal Alignment in Adolescent Idiopathic Scoliosis Patients Following Strategic Pedicle Screw Fixation

Abstract: Study DesignRetrospective observational study.PurposeTo analyze the effect of low-density (LD) strategic pedicle screw fixation on the correction of coronal and sagittal parameters in adolescent idiopathic scoliosis (AIS) patients.Overview of LiteratureLD screw fixation achieves favorable coronal correction, but its effect on sagittal parameters is not well established. AIS is often associated with decreased thoracic kyphosis (TK), and the use of multi-level pedicle screws may result in further flattening of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In doing so, we demonstrated that these deformities are relatively common and that they are not associated with changes in lumbar lordosis (Table 6 and Figure 4). Similar changes in sagittal alignment have been described cephalad [33][34][35][36][37][38][39] and/or caudal [40][41][42] to posterior instrumentation in children with adolescent idiopathic scoliosis. However, we are not aware of any other reports describing these changes we have observed in the SMA population.…”
Section: Discussionsupporting
confidence: 70%
“…In doing so, we demonstrated that these deformities are relatively common and that they are not associated with changes in lumbar lordosis (Table 6 and Figure 4). Similar changes in sagittal alignment have been described cephalad [33][34][35][36][37][38][39] and/or caudal [40][41][42] to posterior instrumentation in children with adolescent idiopathic scoliosis. However, we are not aware of any other reports describing these changes we have observed in the SMA population.…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, Tao et al [ 18 ] reported that TK increased from before to after surgical correction, although the position of terminal fusion was different [ 18 ]. Similarly, a review of 92 cases by Dumpa et al [ 32 ] showed satisfactory recovery of TK in all groups of studies. The results of the current study showed that TK increased in comparison with preoperative and postoperative TK, and the sagittal plane was effectively restored.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast with these statements, in a recent retrospectively observational study, Srikanth Reddy Dumpa et al stated that screw fixation provides favorable coronal correction and improves overall sagittal parameters causing a restoration of TK in patients with hypokyphosis and hyperkyphosis preoperatively 16 .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the three-dimensional direct segmental derotation of the vertebrae provided by pedicle screws is considered another feature that decreases thoracic kyphosis as Kota Watanabe et al studied in a 3D simulation 27 . In contrast with these statements, in a recent retrospectively observational study, Srikanth Reddy Dumpa et al stated that screw fixation provides favorable coronal correction and improves overall sagittal parameters causing a restoration of TK in patients with hypokyphosis and hyperkyphosis preoperatively 16 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation